ISCHEMIC HEART DISEASE - Mukhammadieva Mukarrama Ibrokhimovna (Web of Journals Publishing, 2025)
Ischemic heart disease (IHD), also known as coronary artery disease (CAD), is one of the leading causes of morbidity and mortality worldwide. It occurs due to the narrowing or blockage of coronary arteries, reducing blood flow to the myocardium. This article discusses the pathogenesis, risk factors, clinical manifestations, diagnostic methods, and modern approaches to treatment and prevention of IHD.
Keywords: Ischemic heart disease, coronary artery disease, atherosclerosis, myocardial infarction, treatment, prevention.